Ni-Hard material data and applications - Rohrig, K. (Nickel Development Institute, 1996)
Ni-Hard is the generic name for a family of white cast irons alloyed with nickel and chromium to give high hardness and outstanding resistance to abrasion. This book updates information for users on Ni-Hard's material data and applications.
Cover title.
Keywords: Chromium-iron-nickel alloys.; Cast-iron.; elektronické knihy; electronic books